Constraints Experienced by Dairy Farmers in Adoption of Improved Animal Husbandry Practices - B. K., Ashwar,; K. B, Ashwar; K.L., Patel (Indian Journal of Extension Education, 2017)
The major constraints experienced by the dairy farmers in adoption of improved animal husbandry practices were  inadequate irrigation facilities for growing green fodder for animals (100 %), followed by non-availability of elite sires for  breeding purpose in villages (97.5 %) and too much of repeat breeding through A. I.(96.4 %). The non-availability of  expert services to treat repeat breeders(95 %), lack of knowledge about control measures of clinical and sub clinical  mastitis(93.6 %) and infertility problems in dairy animals(93.3 %), non-availability of input for green fodder(92.8 %),  were also major problems in adoption of improved animal husbandry practices. Measures suggested by the dairy farmers  to overcome the barriers in adoption were to make provision of adequate water for fodder cultivation, improvement of  skill of para- veterinarians and provision of required number of elite bulls for natural services at the village level. Regular  training to dairy farmers, a competitive price for milk products, arrangement for fodder depots, heath services and timely  vaccination were also some of the suggested important needs of dairy farmers.
Keywords: constraints; improved animal husbandry practices; adoption; dairy farmers